CRITICAL REVIEW OF THE USE OF BLOCKCHAIN TECHNOLOGY IN IMPROVING MSME DATA TRANSPARENCY AND SECURITY - Husriadi, Muh.; Bahar, Harmiaty; Windayani, Windayani (Laboratorium Riset Ekonomi, 2024)
The use of blockchain technology in MSMEs is an increasingly important topic to support data transparency and security. The aim of this research is to evaluate the effectiveness of blockchain technology in increasing transparency and data security for SMEs in Mandonga District, Kendari City. The research approach uses descriptive qualitative by involving respondents from MSME actors. The analysis results show that the application of blockchain technology has a positive effect in improving data integrity, reducing security risks and increasing customer trust. The implication of this research is that MSMEs can use blockchain technology to improve their business performance and meet increasingly stringent compliance requirements. Therefore, this research provides a strong theoretical and practical foundation for the application of blockchain technology in the MSME environment and provides valuable insights for practitioners and researchers in the field.